1990
DOI: 10.1002/pen.760301004
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic material characterization and modeling for polyethylene

Abstract: An extensive set of stress relaxation and constant strain rate tests for characterizing the mechanical responses of a medium density polyethylene and a high density polyethylene that are commonly used in natural gas distribution piping is described and analyzed. The development of coherent master curves for the relaxation modulus, maximum stress, and the time‐to‐failure for pressurized pipes through a combination of both horizontal and vertical shifting is presented. The relaxation data are used to develop a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(41 citation statements)
references
References 6 publications
2
39
0
Order By: Relevance
“…However, these mechanical properties are very complicated and have not been sufficiently described yet applying a usual viscoelastic theory. This is because semicrystalline polymers such as polyethylene exhibit a marked deviation from linear viscoelastic behavior even at small strains [1][2][3][4][5] . It has been identified that plastic deformation, such as dislocation, microvoid formation, and the slippage of crystallites, can arise from any applied deformation [6][7][8] and that anharmonic elastic response can be caused by mechanical and thermal excitations 9,10) .…”
Section: Introductionmentioning
confidence: 99%
“…However, these mechanical properties are very complicated and have not been sufficiently described yet applying a usual viscoelastic theory. This is because semicrystalline polymers such as polyethylene exhibit a marked deviation from linear viscoelastic behavior even at small strains [1][2][3][4][5] . It has been identified that plastic deformation, such as dislocation, microvoid formation, and the slippage of crystallites, can arise from any applied deformation [6][7][8] and that anharmonic elastic response can be caused by mechanical and thermal excitations 9,10) .…”
Section: Introductionmentioning
confidence: 99%
“…The shift factor obeys to the WilliamLandel-Ferry (or WLF) equation [7]. In fact, this method is relevant with many amorphous polymers but is not appropriate with semicrystalline thermoplastics for which the time-temperature superposition principle is not valid [8].…”
Section: Introductionmentioning
confidence: 99%
“…[71][72][73] ) or fracture toughness vs. time to fracture data, [58][59][60] respectively, as functions of temperature or loading speed can be brought into superposition (master curves), using Arrhenius-type shift factors obtained by deformation measurements at small amplitudes. [9,15,[74][75][76][77][78] Quantitative Correlations According to Ramsteiner, quantitative correlations between mechanical damping determined by using DMA and the impact strength should not be expected in the whole range of temperature, because DMA probes the range of linear viscoelasticity, whereas the impact test probes the range of non-linear viscoelasticity and processes of damage. [38] (Notwithstanding, the validity of some aspects of the time/temperature superposition principle can be extended to the fracture process, as shown above).…”
Section: Arrhenius Diagrammentioning
confidence: 99%